Coordinated fault‐ride‐through strategy for doubly‐fed induction generators with enhanced reactive and active power support. Issue 2 (1st February 2016) - Liu, Sumei; Bi, Tianshu; Jia, Ke; Yang, Qixun
Abstract : With the fault ride through (FRT) requirement of grid codes, wind generators must stay connected and provide the reactive and active power support during and after the grid faults. The doubly fed induction generators (DFIGs) usually employ an active rotor crowbar to ride‐through the faults. The solution works well to protect the DFIG itself, but it has shortcomings in the power support. In the paper, a coordinated FRT control strategy is investigated to improve the power support capability of the DFIGs under the fault conditions. In this strategy, a seamless switch is designed to resume the power control mode after the short‐term crowbar interruption. Additional compensation terms are inserted into the converter's control loops to relieve the side‐effect of rotor transient current. The coordinated control of dc‐chopper circuit and rotor‐side converters is proposed to keep the dc‐link voltage within its acceptable range. Moreover, a novel voltage limiter is designed with consideration of the conflicting effect of rotor transient current, converter's rating constraints and desired power goals. Compared with the conventional crowbar‐based strategies, the proposed strategy can fully utilise the DFIG's potential to generate reactive and active power effectively. These performances have been demonstrated through the simulation and experimental tests.